A decade in review: bibliometric analysis of sustainable performance trends in higher education institutes - Umar, Shahawati Binti; Ahmad, Jawaria; Bukhori, Muhammad Anas Bin Mohd; Mohd Ali, Khairul Anuar; Wan Hussain, Wan Mohd Hirwani (Frontiers in Education, 2024)
Sustainable performance of higher education institutes (HEIs) is key to manage the educational institutes efficiently in the long run, to get financial aid from Government and to keep the interest of stakeholders in the institutions. Researchers have focused on examining the impact of sustainable curriculum, sustainable teaching methodologies, sustainable campuses and assessment of tools for assessing sustainability in HEIs in past literature. The present bibliometric analysis combined with network analysis aims to explore the literature to identify research gaps in the field of sustainable performance or sustainability performance of HEIs. We have employed a PRISMA flow diagram to analyze the results obtained from Scopus, Web of Science (WoS) and EBSCOhost databases. A bibliometric analysis using biblioshiny and VOSviewer software was performed on the 263 papers included in the study after screening. The results revealed that annual growth rate of publications is increasing indicating that the sustainability performance of HEIs is gaining momentum after introduction of the Sustainable Development Goals (SDGs) in 2017. The production of articles in the field is highest from advanced European countries and America, and few articles are published from Asian countries. The authors with the highest number of publications and the most cited research paper in the field are Leal Filho and Wals respectively. Author's keyword higher education institutes (or institutions) has a strong link with sustainability, sustainable education, green campus and sustainability assessment whereas has a small network with sustainable performance, green knowledge sharing, green knowledge management, green human resource management practices, green teams, change management, and organizational commitment. These findings can be used by future researchers to identify unexplored research areas in different contexts.